Optimization of Water Guarantee for Making Face Cleaning Soap - Yulia Vera; Susi Yanti (Journal of Public Health and Pharmacy, 2022)
Facial cleansers generally have good cleaning power. Facial cleansing soap is also very necessary to keep facial skin clean and healthy. One of the natural ingredients that can help the cleaning process is guava leaf water. Guava leaf water contains several secondary metabolites, such as tannins, triterpenoids, glycosides and flavonoids. In addition, the selection of dosage forms also affects the cleaning power of a cleaning soap. Therefore, in this study, a cleaning soap was made from guava leaf water and a physical evaluation of the soap was carried out in accordance with the specifications and requirements specified. The principle of the saponification reaction is the reaction between oil and KOH/NaOH. The facial cleansing soap made in this study is solid soap. Based on the quality test results, solid leri soap has a pH of 10.3, the saponification rate is 32 water content 34 water content 34% and respondent tests on the aroma and foam aspects which show good enough results so that guava water treatment can be an alternative solution to prevent the use of water. Facial cleanser that contains harmful chemicals.